A new species of flea-toad (Anura: Brachycephalidae) from southern Atlantic Forest, Brazil - Condez, Thais Helena; Monteiro, Juliane Petry De Carli; Comitti, Estevão Jasper; Garcia, Paulo Christiano De Anchietta; Amaral, Ivan Borel; Haddad, Célio Fernando Baptista (Zootaxa, 2016)
We describe a new species of Brachycephalus that is morphologically similar to the flea-toads B. didactylus, B. hermogenesi, and B. pulex. The new species occurs from the sea level up to 1000 m and it is widely distributed throughout southern Atlantic Forest. Brachycephalus sulfuratus sp. nov. is distinguished from all of its congeners by the combination of the following characters: (1) small body size (SVL of adults: 7.4–8.5 mm for males and 9.0–10.8 mm for females); (2) “leptodactyliform” body; (3) pectoral girdle arciferal and less robust compared to the Brachycephalus species with “bufoniform” body; (4) procoracoid and epicoracoid fused with coracoid but separated from the clavicle by a large fenestrae; (5) toe I externally absent; toes II, III, IV, and V distinct; phalanges of toes II and V reduced; (6) skin smooth with no dermal ossifications; (7) in life, general background color brown with small dark-brown spots; skin of throat, chest, arms, and forearms with irregular yellow blotches; in ventral view, cloacal region of alive and preserved specimens surrounded by a dark-brown inverted v-shaped mark outlined with white; (8) advertisement call long, composed of a set of 4–7 high-frequency notes (6.2–7.2 kHz) repeated regularly.